Comparison of three infant venous reservoirs with vacuum-assisted venous drainage during varying levels of cardiotomy suction. (January 2020) - Shade, Brandon C; Melchior, Richard W; Fisher, Douglas R; High, Robin; Mascio, Christopher E; Rosenthal, Tami M; Holt, David W
Background: Vacuum-assisted venous drainage has gained widespread use within the pediatric perfusion community for use during cardiopulmonary bypass. It is questioned whether its efficiency may be compromised with application of excessive cardiotomy suction to the infant hard-shell venous reservoir. An in vitro simulation circuit was used to research this phenomenon. A comparison of three different infant hard-shell venous reservoirs also took place to determine if one reservoir type was more advantageous when handling cardiotomy suction. The reservoirs tested were the Maquet VHK 11000, Medtronic Affinity Pixie, and Terumo Capiox FX05. Methods: The in vitro simulation circuit consisted of a 1 L reservoir bag that was cannulated at one access point with an Edwards Lifesciences 10Fr aortic cannula and the other access area with an Edwards Lifesciences 10Fr right angle venous cannula and 12Fr right angle venous cannula that were joined together. Key points of measurement and response variables were the pressures on the connection of the venous cannulas, inlet of the venous reservoir, and flow through the venous line. Vacuum was applied and manipulated with a Maquet VAVD Controller to settings of −20 mmHg, −30 mmHg, –40 mmHg, −50 mmHg, and −60 mmHg. Cardiotomy suction was added at settings of 1 LPM, 2 LPM, 3 LPM, and 4 LPM. Values from each response variable were monitored and recorded. These data were utilized to compare the reservoirs with a random coefficient model for each response variable. Conclusions: There is an adverse effect of excessive cardiotomy suction on the efficacy of vacuum-assisted venous drainage in infant hard-shell venous reservoirs. There is no significant difference between the VHK 11000, Pixie, and FX05 regarding their ability to handle this occurrence. An important discovery was that the FX05 showed a greater transfer of vacuum to the venous cannulas and reservoir inlet.